Robôs afetivos, bonecas do amor e personagens irresistíveis: um estudo sobre as paixões transdimensionais no Japão - Aoki, Beatriz Yumi (2022)
In recent years, with the technological development of robotics in Japan, the discussion about the insertion of robots in everyday life has become increasingly present. The main objective of this thesis is to analyze the genesis of these new robots, emphasizing on transdimensional affective relationships, which have also been constructed with other objects such as dolls, characters and vocaloid characters. The main hypothesis is that, in situations of precariousness (loneliness, loss and illness) it is the affective robots that confer the status of person to the human beings with whom they relate, and not the opposite, as it is usually thought from an anthropocentric point of view. The methodology is based on field research, conducted in Japan between 2019 and 2020, including visits to advanced study centers, robotics laboratories and exhibitions; in addition to an extensive literature review. The research is structured in three main parts called episodes, as if they were chapters or events of the research trajectory. The first and second parts discuss transdimensional relationships in Japan, and in the third and last chapter, we create an overview of the state of the art of robot development, focusing on ethical issues and power relations that permeate the discussions. In addition to the specific bibliography collected in Japan, we articulate a network of academic researchers who analyze the relationships between bodies (animate and inanimate) and technological devices, among which Katz and Greiner, Agnès Giard, Jennifer Robertson, Mel Chen, Hiroki Azuma, Roberto Esposito, among others. As a result, it is expected that the research will collaborate with the area of communication and arts, since it proposes new questions around the complex relationships between humans and robots